FRI0058 THE IMPORTANCE OF SPECKLE TRACKING ECHOCARDIOGRAPHY IN THE EVALUATION OF CARDIAC FUNCTIONS IN PATIENTS WITH RHEUMATOID ARTHRITIS. (2nd June 2020) - Ebik, M.; Taştekin, N.; Gürdoğan, M.; Ebik, M.; Birtane, M.; Emmungil, H.; Yilmazer, B.; Süt, N.
Abstract : Background: Rheumatoid arthritis (RA) is an inflammatory disease that includes chronic, progressive joint arthritis and also has multi-systemic involvement. It is known that the acceleration of many cardiovascular diseases causing mortality and morbidity, especially atherosclerosis and heart failure, is increased in RA patients. Objectives: In this study, it was aimed to analyze the layer-specific (endocardial, transmural and epicardial) strain values obtained by speckle tracking echocardiography method in the determination of subclinical cardiac dysfunction in RA patients and to determine the correlation between anti cyclic citrullized peptide (Anti-CCP) titers, disease activity score (DAS-28), disease duration and strain values. Methods: This study was performed with 63 RA patients and 31 healthy participants. The patients were grouped as <5 years, 5-10 years and >10 years according to their disease duration. DAS28-CRP was used to determine disease activation. The standard assessment included complete serum concentration of C-reactive protein, Anti-CCP, Romatoid faktör (RF), N-terminal pro b-type natriuretic peptide (NT-proBNP) and homocysteine. Endocardial, transmural and epicardial strain values were analyzed by M-mode, 2D, tissue doppler and speckle tracking echocardiography. Results: When the groups were compared in terms of laboratory data, NT-proBNP value of RA patients was higher than the control group (p=0.044), homocysteine level was similar (p>0.05). When the groups were compared in terms of conventional echocardiographic parameters, ejection fraction of the control group was similar (p>0.05). E/A and E/E' ratios were found to be significantly different (p<0.001, p=0.015). When the groups were compared in GLS values obtained by speckle tracking echocardiography, endocardium, transmural and epicardium GLS values were lower in RA patients (p<0.05) (Table 1 ). As the disease duration increased, GLS values were found to be worse (p<0.05). There was a significant correlation between RA disease activity scores level and LV GLS value, increasing levels of disease activity was associated with worse LV GLS (r=0.583, p<0.01 and r=0.681, p<0.01 ve r=0.689, p<0.01 for endocardium, transmural and epicardium respectively. There was a significant correlation between anti-CCP, RF and LV GLS value, higher Anti-CCP and RF titers were associated with worse LV GLS (r=0.467, p<0.01 and r=0.509, p<0.01 and r=0.551, p<0.01) for endocardium, transmural and epicardium respectively. Conclusion: The layer-specific global longitudinal strain values obtained by speckle tracking echocardiography were found to be decreased in RA patients. This study, which has been shown to decrease strain values before the reduction of ejection fraction values obtained by conventional methods, may be a guide for the clinician in early detection of cardiac dysfunction in RA patients with high DAS-28 score, long disease duration, high Anti-CCP and high RF titers. References: [1]Corrao S, Argano C, Pistone G, Messina S, Calvo L, Perticone F. Rheumatoid arthritis affects left ventricular mass: Systematic review and meta-analysis. Eur J Intern Med 2015;26(4): 259-67. Disclosure of Interests: None declared